Edukasi Pemanfaatan Informasi Lingkungan Menuju Eliminasi Zero Malaria Di Daerah Resetlemen Pulau Osi Kabupaten Seram Barat - Salakory, Melianus; Tetelepta, Gland E (Program Studi Pendidikan Geografi Universitas Pattimura, 2023)
Data on The Ministry of Health Indonesia 2022 showed that some areas succesfull to eliminate malaria. In Java - Bali has been 121 district and cities declared eliminate malaria by 95%, wherereas Maluku and NTT has been 3 of 33 district and cities with elimination eare by 9%, Papua has been 42 district and cities with elimination rate by 0%, Kalimantan and North Maluku has been 29 of 60 district and cities with elimination rate by 44% and Sumatera, Sulawesi, NTB has been 165 of 245 district and cities with elimination rate by 67%. In this situation, health behavior changes with communication risk approach need to implement in the prevention, treatment and rehabilitation environmental risk og malaria in Osi Island communites. Therefore, they could determine right action to protection themselves. The implementation methodology was education based on Project Base Learning Approach that combine a discourse, discussion and field practices method. Scenario projected was preparation, (developing education and learning plan), actions and closure. The result showed Jumantic cadres had a knowledge of health and free malaria, collecting waste from yard and garden, remove stagnant water, draining a water reservoir, create a simple mosquito repellent based material reduces, slept under mosquito net and observation a larva of mosquito. Jumantic cadres must be empowered by School to help the government and communities towards Zero Malaria Elimination as national policy